Optimasi Dan Formulasi Sediaan Gel Ekstrak Etanol Hydrocotyle Verticillata Thub Dengan Variasi Konsentrasi HPMC Dengan Penambahan Asam Usnat - Habibie Deswilyaz Ghiffari; Alqushay Alqushay; Sri Budiasih; Tommy Julianto (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Hydrocotyle verticillata Thub is a plant that can be used to treat burns. Usnic acid can inhibit pathogenic microorganisms and can act as an anti-inflammatory, both of which can contribute to the wound healing process. The aim of this research is to determine the extract of gotu kola leaves which is formulated into a gel preparation. Gel is a semi-solid system produced by small particles or large organic molecules that penetrate through a liquid. The gel is easy to use, easily absorbed into the skin, and contains soothing and moisturizing properties that have a healing effect. Gel formulations were made with varying concentrations of HPMC F1 (8%), F2 (8%), F3 (8%), F4 (9%), F5 (10%). The gel produced organoleptically has a distinctive gel aroma, green to brownish in color. In the homogeneity test, all preparations were homogeneous and there were no granules, the pH test showed a pH value ranging from 5.17-6.36, the spreadability test was 5.1-6.4 cm. In the viscosity test, the results were 9,250-40,000 cps, the adhesion test obtained results in 13-64 seconds and the cycling test was stable during storage. Based on the research that has been carried out, it can be concluded that the ethanol extract of gotu kola leaves (Hydrocotyle verticillata Thub)can be formulated into a gel preparation and the results of the physical evaluation of the ethanol extract gel preparation of gotu kola leaves(Hydrocotyle verticillata Thub) with varying concentrations of HPMC and the addition of usnic acid are satisfactory. condition.